Epigenetic Repression of Interleukin 2 Expression in Senescent CD4⁺ T Cells During Chronic HIV Type 1 Infection - Nakayama-Hosoya, Kaori; Ishida, Takaomi; Youngblood, Ben; Nakamura, Hitomi; Hosoya, Noriaki; Koga, Michiko; Koibuchi, Tomohiko; Iwamoto, Aikichi; Kawana-Tachikawa, Ai (The Journal of infectious diseases, 2015)
The molecular mechanisms for IL2 gene-specifìc dysregulation during chronic human immunodeficiency virus type 1 (HIV-1) infection are unknown. Here, we investigated the role of DNA methylation in suppressing interleukin 2 (IL-2) expression in memory CD4⁺ T cells during chronic HIV-1 infection. We observed that CpG sites in the IL2 promoter of CD4⁺ T cells were fully methylated in naive CD4⁺ T cells and significantly demethylated in the memory populations. Interestingly, we found that the memory cells that had a terminally differentiated phenotype and expressed CD57 had increased IL2 promoter methylation relative to less differentiated memory cells in healthy individuals. Importantly, early effector memory subsets from HIV-1-infected subjects expressed high levels of CD57 and were highly methylated at the IL2 locus. Furthermore, the increased CD57 expression on memory CD4⁺ T cells was inversely correlated with IL-2 production. These data suggest that DNA methylation at the IL2 locus in CD4⁺ T cells is coupled to immunosenescence and plays a critical role in the broad dysfunction that occurs in polyclonal T cells during HIV-1 infection.